PENGARUH KONDISI SOSIAL EKONOMI TERHADAP KEJADIAN STUNTING DI INDONESIA - Ade Nurul Aida (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2019)
This analysis aims to determine the effect of socioeconomic conditions on the incidence of stunting in Indonesia during 2015-2018. The analysis uses the fixed effect method with secondary data in the form of panels consisting of 34 provinces in Indonesia sourced from the Indonesian Ministry of Health and the Central Statistics Agency (BPS). Based on the results of the analysis shows that the socioeconomic status of family income and conditions of poverty levels, as well as infants who receive exclusive breastfeeding, the level of protein consumption, households that have access to proper sanitation simultaneously have an influence on stunting. In addition, this analysis also shows that family income has a negative and significant effect on stunting, so it can be concluded that the greater the income in the family, the smaller the stunting event that occurs. While the poverty rate has a negative effect on the incidence of stunting, statistically the effect is not significant.